Prevalence of polypharmacy and potentially inappropriate medication use in older lung cancer patients: A systematic review and meta-analysis - Tian, Fangyuan; Chen, Zhaoyan; Zhou, Dan; Mo, Li (Frontiers in Pharmacology, 2022)
Objectives: In older lung cancer patients, polypharmacy and the use of potentially inappropriate medications (PIM) were commonly reported, but no systematic review and meta-analysis have been carried out to ascertain t the prevalence and risk variables in this group. This study aimed to identify the prevalence of polypharmacy, PIM use and associated risk variables in elderly lung cancer patients. Methods: We looked for articles from the beginning to February 2022 in PubMed, Embase, and Web of Science that related the use of PIM and polypharmacy by older lung cancer patients (PROSPERO Code No: CRD42022311603). Meta-analysis was performed on observational studies describing the prevalence and correlation of polypharmacy or PIM use in elderly patients with lung cancer. Results: Of the 387 citations, 6 articles involving 16890 patients were in the final sample. In older lung cancer patients pooled by meta-analysis, 38% and 35%, respectively, of PIM use and polypharmacy. The prevalence of PIM use was 43%, 49%, and 28%, respectively, reference to the 2019 Beers criteria, 2014 STOPP/START criteria, and other criteria. Conclusion: This systematic review and meta-analysis demonstrated a high prevalence of polypharmacy and PIM use among older lung cancer patients. Therefore, it is essential to take rational interventions for elderly lung cancer patients to receive reasonable pharmacotherapy.